Analisis Penegakan Hukum terhadap Tindak Pidana Korupsi yang Dilakukan oleh Pejabat Tinggi Militer - Revony Lede Rihi; Heryanto Amalo; Adrianus Djara Dima (Lembaga Pengembangan Kinerja Dosen, 2025)
Corruption crimes are not only committed by civilians, but can be committed by military soldiers, namely the TNI who are educated with discipline. The handling of corruption cases committed by TNI soldiers together with civilians is handled through a connexity trial regulated in the Criminal Procedure Code. Although there are rules governing, there are still discrepancies in law enforcement. The main problems in this study are: (1) Is it appropriate for corruption cases committed by military officials to be tried in the Military Court? (2) What are the obstacles in law enforcement against high-ranking military officials who commit corruption crimes?This research is normative legal research, namely by examining literature or legal materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Normative legal research is a scientific research procedure to find the truth based on the logic of legal science from its normative side. The results of this study indicate that: (1) is it appropriate for corruption cases by military officials to be tried in the Military Court: The handling of corruption cases in Basarnas involving active military personnel who are tried in military courts is considered inappropriate because it will create an impression of inconsistent law enforcement, because it contradicts the provisions of Law No.8 of 1981 concerning the Criminal Procedure Code and Law No.48 of 2009 concerning Judicial Power. (2) Obstacles in law enforcement against high-ranking military officials who commit corruption crimes: Corruption crimes involving active military members stem from disharmonization of laws in the provisions of the Military Justice Law, Corruption Court Law, TNI Law, KPK Law, and Criminal Procedure Code. The researcher's suggestion is that to minimize the differences of opinion that continue to emerge, an extensive regulation on connexity should be made so that it can serve as a guideline in handling corruption cases involving military personnel and civil society.